Performance-related physiological changes induced by one year of endurance training in young athletes - Christina Mishica; Christina Mishica; Heikki Kyröläinen; Maarit Valtonen; Hans-Christer Holmberg; Vesa Linnamo; Vesa Linnamo (Frontiers Media S.A., 2023)
IntroductionAlthough maximal oxygen uptake (VO2max) is generally recognized as the single best indicator of aerobic fitness in youth, interpretation of this parameter and the extent to which it can be improved by training remain controversial, as does the relative importance of VO2max for performance in comparison to other factors such as power production. Here, we examined the influence of endurance training on the VO2max, muscle power and sports-related performance of cross-country skiers attending a school specializing in sports, as well as potential relationships between any changes observed to one another and/or to perceived stress scale (Cohen) and certain blood parameters.MethodsOn two separate occasions, prior to the competition season and separated by one year of endurance training, the 12 participants (5 males, 7 females, 17 ± 1 years) carried out tests for VO2max on a treadmill, explosive power utilizing countermovement jumps (CMJ) and ski-specific maximal double pole performance (DPP) employing roller skis on a treadmill. Blood levels of ferritin (Fer), vitamin D (VitD) and hemoglobin (Hg) were monitored, and stress assessed with a questionnaire.ResultsDPP improved by 10 ± 8% (P < 0.001), but no other significant changes were observed. There were no significant correlations between the changes in DPP and any other variable.DiscussionWhereas one year of endurance training improved the cross-country ski-specific performance of young athletes significantly, the increase in their maximal oxygen uptake was minimal. Since DPP was not correlated with VO2max, jumping power or the levels of certain blood parameters, the improvement observed probably reflected better upper-body performance.